(untitled) (Global Journal of Science Frontier Research, 2023)
Fish meal FM has excellent protein and lipid profile However FM is losing its acceptability and substituted with plant protein due to high price high demand and sustainability issues in global aquaculture production In this study experimental diets were prepared by substituting FM with soybean meal SM to assess the effects on growth performance The study was carried out by rearing 240 Oreochromis niloticus fries 0 1g in 12 hapa in earthen pond for 65 days in Kathar Chitwan The fishes were fed with four isonitrogenous 27 protein and isocaloric experimental diets viz Treatment T1 100 fish meal protein Treatment T2 50 fishmeal protein and 50 soybean meal protein Treatment T3 25 fishmeal protein and 75 soybean meal protein and Treatment T4 100 soybean meal protein Among the treatments the weight gain mean harvest weight specific growth rate was obtained with no significant difference p 0 05 was observed between treatment T1 T2 and T3 but shows statistically significance difference with treatment T4 Treatment T3 1 35 have higher B C ratio than other treatment implies to economical farming composition All water quality parameters like temperature dissolved oxygen pH turbidity and ammonia etc measured during the experimental period were found at the desired level So the study concludes that fish meal protein can be replaced upto 75 by soybean meal protein in the diet of O niloticus without affecting the growth performance